Prefrontal modulation of anxiety through a lens of noradrenergic signaling - Bouras, Nadia N.; Mack, Nancy R.; Gao, Wen-Jun (Frontiers in Systems Neuroscience, 2023)
Anxiety disorders are the most common class of mental illness in the U.S., affecting 40 million individuals annually. Anxiety is an adaptive response to a stressful or unpredictable life event. Though evolutionarily thought to aid in survival, excess intensity or duration of anxiolytic response can lead to a plethora of adverse symptoms and cognitive dysfunction. A wealth of data has implicated the medial prefrontal cortex (mPFC) in the regulation of anxiety. Norepinephrine (NE) is a crucial neuromodulator of arousal and vigilance believed to be responsible for many of the symptoms of anxiety disorders. NE is synthesized in the locus coeruleus (LC), which sends major noradrenergic inputs to the mPFC. Given the unique properties of LC-mPFC connections and the heterogeneous subpopulation of prefrontal neurons known to be involved in regulating anxiety-like behaviors, NE likely modulates PFC function in a cell-type and circuit-specific manner. In working memory and stress response, NE follows an inverted-U model, where an overly high or low release of NE is associated with sub-optimal neural functioning. In contrast, based on current literature review of the individual contributions of NE and the PFC in anxiety disorders, we propose a model of NE level- and adrenergic receptor-dependent, circuit-specific NE-PFC modulation of anxiety disorders. Further, the advent of new techniques to measure NE in the PFC with unprecedented spatial and temporal resolution will significantly help us understand how NE modulates PFC function in anxiety disorders.